The Comparison of Elementary Educational Curriculum between Indonesia and Finland - Efendi, Moch. Yusuf (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
Indonesia's education system is still not able to fully answer the needs and global challenges for the future. The program of equity and improvement of education quality is a prominent problem in Indonesia. Meanwhile, the number of people at the age of primary education not included in the national education system is still very high. The education environment in Indonesia is still faced with a variety of internal problems that are fundamental and complex. In addition, the Indonesian people still face a number of problems from the basic education to higher education. The quality of education in Indonesia is still far from being expected. It is different from Finland. The government and people realize that a strong commitment to build and develop a national education system is a key determinant of the success of the state to maintain its survival as a small, resource-limited nation living in extreme and less friendly conditions. The development of the nation and nation stands on the pillars of innovation-based education and research and is fully supported by all components of the nation. This paper is expected to be an inspiration for readers to improve the quality of education in Indonesia.The method used is to use a comparative method with a literature review in which the literature related to the topics of the problem is collected, grouped, analyzed and formulated to obtain the differences that are then selected for development into the education curriculum in Indonesia. From the comparative methodology, there are several findings and can be applied in the curriculum of primary schools in Indonesia such as the education system, the implemented curriculum, and the teaching innovation and teachers.